Properties of melarsamine hydrochloride (Cymelarsan) in aqueous solution. - Berger, B J (1994)
The antitrypanosomal drug melarsamine hydrochloride (MelCy) (trade name, Cymelarsan) is a melamino-phenylarsine made by conjugation of one equivalent of melarsen oxide and two equivalents of cysteamine. Immediately after it was dissolved in water, the compound was found to exist as an equilibrium mixture containing MelCy (43%), MelCy which had lost one cysteamine moiety (MelCy -1; 24%), melarsen oxide (33%), and free cysteamine. Small amounts (< 1%) of the oxidation products derived from the last two components were also formed (cystamine and sodium melarsen). On incubation at room temperature, the MelCy content decreased steadily, with an associated increase in the melarsen oxide and sodium melarsen contents. After 5 days in solution at room temperature, 27% of the arsenical agent was MelCy, 14% was MelCy -1, 42% was melarsen oxide, and 17% was sodium melarsen. Since H2O2 production was detectable in MelCy or cysteamine solutions and the addition of small amounts of exogenous H2O2 readily converted the trivalent melarsen oxide to the pentavalent sodium melarsen, it is hypothesized that the nonenzymatic conversion of cysteamine to cystamine produced H2O2, which then oxidized melarsen oxide to sodium melarsen. Similar time course experiments showed that melarsonyl potassium and melarsoprol were more stable in solution.